2020
DOI: 10.21203/rs.3.rs-76069/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circular RNA circFADS2 is Overexpressed in Sepsis and Suppresses LPS-Induced Lung Cell Apoptosis by Inhibiting the Maturation of miR-15a-5p

Abstract: Circular RNA circFADS2 plays protective roles in LPS-induced inflammation, which promotes sepsis, suggesting its involvement of circFADS2 in sepsis. We then analysis the involvement of circFADS2 in LOS Expression of circFADS2, mature miR-15a-5p and miR-15a-5p precursor in plasma samples (collected at two time points) from sepsis patients (n=60) and healthy controls (n=60) was determined by RT-qPCR. The expression vector of circFADS2 was transfected in lung cells, followed by the measurement of the expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…We suspected that in pathological conditions, some unknown pathological factors drive the altered expression of circFADS2/miR-133a axis, which deserves to be further studied. Hong et al reported that circFADS2 is overexpressed in sepsis, and LPS treatment increased circFADS2 expression in a does-dependent manner [29]. In this study, we found circFADS2 is downregulated in sepsis, and LPS treatment inhibited circFADS2 expression in a does-dependent manner.…”
Section: Discussionsupporting
confidence: 64%
“…We suspected that in pathological conditions, some unknown pathological factors drive the altered expression of circFADS2/miR-133a axis, which deserves to be further studied. Hong et al reported that circFADS2 is overexpressed in sepsis, and LPS treatment increased circFADS2 expression in a does-dependent manner [29]. In this study, we found circFADS2 is downregulated in sepsis, and LPS treatment inhibited circFADS2 expression in a does-dependent manner.…”
Section: Discussionsupporting
confidence: 64%
“…Among the more interesting candidates are microRNA (miRNA) [120][121][122][123] and circular RNA (circRNA), 124,125 which can play a prominent role in regulating the immune system. 121,126,127 In vivo measurement capabilities are not yet available.…”
Section: Other Biomarkers Of Inflammationmentioning
confidence: 99%